Balancing work and family life, by the midwives of Porto Novo - TAOUEMA, Bienvenue; AKEREBOUROU, Bernyx (My University, 2022)
African culture gives men and women different complementary roles, so that the tasks of the house are rather taken in hand and carried out by the woman. Currently, in addition to their tasks as women in the family, like men, they are on the job market to earn additional financial resources from the family or their own autonomy and emancipation. How do they reconcile the successful completion of the activities of their lives: family and professional? The reflection on "the reconciliation of family life activities and professional life", if it is in vogue in the West is recent in French-speaking black Africa and especially in Benin. For our study we have chosen a population of women from the city of Porto Novo, having a very active profession: midwives, and who have a family life. Data was obtained and analyzed through: a questionnaire administered to a sample of thirty (30) subjects; of six (06) interviews. Then an analysis model obtained from theories: of conflict, maximization and overflow, in relation to the reconciliation of professional and family activities. The very interesting results of this study, which sufficiently shows its usefulness, share the tips of these ladies to properly assume their responsibilities.
Keywords: reconciliation; professional life; family life; conflict; time; stress; strategy